Cement cooling coating and cement cooling building material
By developing cement-quality cooling coatings and building materials containing composite cement, structural fillers, water-absorbing polymers, water collection materials and dispersants, the dual methods of radiation cooling and evaporative cooling are adopted to solve the problem that the cooling effect in the existing technology depends on environmental conditions and mechanical characteristics, and the efficient and environmentally friendly passive cooling effect is achieved and light pollution is avoided.
Patent Information
- Application Number
- CN202380066268.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-25
AI Technical Summary
The existing technology has problems such as performance dependence on environmental conditions, insufficient mechanical characteristics and light pollution in cooling coatings and building materials, making it difficult to effectively achieve continuous passive cooling in tropical countries.
A cement-quality cooling coating and building material is developed, containing composite cement, structural fillers, water-absorbing polymers, water collection materials and dispersants. Through the dual passive cooling method of radiation cooling and evaporative cooling, nanoparticles and porous structures are combined to improve solar reflectivity and thermal emissivity.
It achieves a significant reduction in the temperature of the building surface in a hot environment, provides an efficient passive cooling effect, while avoiding light pollution, and enhancing the mechanical strength and scratch resistance of the building.
Smart Images

Figure CN119894993A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority to Singapore Patent Application No. 10202251097A filed on September 21, 2022 and Singapore Patent Application No. 10202251226B filed on September 30, 2022, the contents of which are incorporated herein by reference in their entirety for all purposes. Technical Field
[0003] The present application relates to a cementitious cooling paint and a cementitious cooling building material. Specifically, the present application relates to a cementitious cooling paint and a cementitious cooling building material, which present a dual passive cooling mode including radiation cooling and evaporation cooling. Background Art
[0004] Passive radiative cooling technology is a new method for continuous energy-saving surface cooling. Its cooling effect requires the cooling material to have an ultra-high thermal emissivity within the atmospheric window (8μm to 13μm). In hot seasons, the solar power density in different regions can be 800W / m 2 Up to 1200W / m 2 , and such high sunlight intensity is not conducive to outdoor cooling. Therefore, strong sunlight reflection is as important as long-wavelength infrared (LWIR) emission for sustained passive cooling. However, the coating manufacturing usually involves organic solvents that are not environmentally friendly because of their strong structural or bonding properties. Most importantly, the performance of passive radiative cooling coatings is highly dependent on environmental conditions, such as relative humidity, where higher relative humidity significantly weakens the cooling effect. In addition, the performance of radiative cooling materials, which is heavily dependent on the radiation angle, varies significantly on the applied surface, hindering its applicability potential.
[0005] Conventional coatings for buildings are mainly used for protection purposes (with good mechanical strength) and decorative purposes (with smooth surfaces and different colors). Some commercial cooling paints are usually very white in color for strong sunlight reflection, but due to their low thermal emissivity within the atmospheric window, the paint has poor passive radiation cooling ability. However, neutral white paint is limited in most building coating applications because neutral white paint can cause light pollution under strong sunlight, especially for the side walls of buildings. Due to the fundamental limitation of the working principle of radiative cooling materials, for side wall applications, radiative cooling materials are always subject to constrained cooling performance due to insufficient radiation angle with the sky.
[0006] As for building materials, they are mainly made of cement containing sand due to their low cost and good mechanical properties. Conventional concrete has a darker color that usually absorbs sunlight, and therefore most buildings require a solar reflective coating on the concrete surface to reduce solar heating. However, due to the reflectivity upper limit of the building surface, which is usually below 85% (to reduce light pollution), a large amount of solar energy still heats the surface, which leads to an undesirable cooling effect. Tropical countries have higher ambient temperatures, higher relative humidity, and stronger solar radiation (up to 1200W / m 2 These countries have higher active energy consumption because the use of air conditioning for indoor cooling has increased significantly over the past few decades.
[0007] In addition to radiative cooling, water evaporation is another passive process that continuously consumes heat energy. Evaporative cooling has been applied in the Egyptian accident by water spraying or equivalent methods. However, long-lasting and water-saving evaporative cooling requires a medium that can accommodate a large amount of water. For this reason, a hydrogel-based coating has recently been developed for evaporative cooling because it exhibits an extremely high water content. However, the poor mechanical properties of hydrogel-based coatings in terms of load bearing and scratch resistance limit its potential in the construction industry.
[0008] Therefore, it is desirable to provide a cementitious cooling coating and a cementitious cooling building material, which seek to solve at least one of the above problems or at least provide an alternative solution. Summary of the invention
[0009] According to a first aspect, the present disclosure provides a cementitious cooling paint. The cementitious cooling paint comprises composite cement; structural filler; water-absorbing polymer; water-collecting material; and water; wherein the mass ratio of water to composite cement is 0.4 to 1.2; the mass ratio of composite cement to structural filler is 0.4 to 0.7; the mass ratio of composite cement to water-absorbing polymer is 0.01 to 0.03; and the mass ratio of composite cement to water-collecting material is 0.05 to 0.3.
[0010] In some embodiments, the cementitious cooling paint further comprises a dispersant, wherein the mass ratio of the composite cement to the dispersant is 20 to 50.
[0011] According to a second aspect, the present disclosure provides a cementitious cooling building material, which comprises composite cement; structural filler; water-absorbing polymer; water-collecting material; dispersant and water; wherein the mass ratio of water to composite cement is 0.5 to 1.5; the mass ratio of composite cement to structural filler is 0.4 to 0.7; the mass ratio of composite cement to water-absorbing polymer is 0.01 to 0.03; the mass ratio of composite cement to water-collecting material is 0.05 to 0.3; and the mass ratio of composite cement to dispersant is 8 to 15.
[0012] In some embodiments, the cementitious cooling building material further comprises alkaline water for hydrating the cementitious cooling building material and preventing the cementitious cooling building material from cracking.
[0013] According to a third aspect, the present disclosure provides a cement-based building product comprising the cementitious cooling building material of the present disclosure. In some embodiments, the cement-based building product is selected from one of cooling tiles, cooling bricks, cooling concrete, cooling concrete blocks, cooling concrete panels and cooling cement walls.
[0014] According to a fourth aspect, the present disclosure provides a set of components including the cementitious cooling coating defined in the present disclosure. The set of components includes a first part, the first part contains a solid mixture consisting of composite cement and structural filler; and a second part, the second part contains a liquid mixture consisting of water-absorbing polymer, water-collecting material, dispersant and water; wherein the mass ratio of water to composite cement is 0.4 to 1.2; the mass ratio of composite cement to structural filler is 0.4 to 0.7; the mass ratio of composite cement to water-absorbing polymer is 0.01 to 0.03; the mass ratio of composite cement to water-collecting material is 0.05 to 0.3; and the mass ratio of composite cement to dispersant is 20 to 50.
[0015] According to a fourth aspect, the present disclosure provides a method for manufacturing a cement-based building product comprising the cement-based cooling building material of the present disclosure. The method comprises mixing composite cement with structural filler to form a solid mixture; mixing a water-absorbing polymer with a water-collecting material, a dispersant and water to form a liquid mixture; uniformly mixing the solid mixture with the liquid mixture to form a cement-based cooling building material precursor; hydrating the cement-based cooling building material precursor using alkaline water to prevent cracks from being generated in the cement-based cooling building material precursor; and molding the hydrated cement-based cooling building material precursor into a desired cement-based building product.
[0016] In some embodiments, the mass ratio of water to composite cement is 0.5 to 1.5; the mass ratio of composite cement to structural filler is 0.4 to 0.7; the mass ratio of composite cement to water-absorbing polymer is 0.01 to 0.03; the mass ratio of composite cement to water-collecting material is 0.05 to 0.3; and the mass ratio of composite cement to dispersant is 8 to 15. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Different embodiments of the present disclosure will be described below in the detailed description with reference to the following drawings:
[0018] Figure 1 is a schematic diagram of the components of a cementitious cooling coating according to some embodiments of the present disclosure.
[0019] Figure 2 It is a schematic diagram of the working mechanism of cementitious cooling paint when applied on the surface of building materials.
[0020] Figure 3A is a graph showing the ratio of water accumulated during rainfall (liquid accumulation) and when there is no sunlight (vapor accumulation).
[0021] Figure 3B is a graph showing a thermogravimetric analysis (TGA) curve, which shows the total water storage capacity of the cementitious temperature reducing coating of the present disclosure and its thermal stability.
[0022] Figure 3C The results of the pore volume test and the visualization test are shown, where the inset is a micro-CT scanning image.
[0023] Figure 3D Differential scanning calorimeter (DSC) curve showing the evaporation performance of cementitious cooling coating.
[0024] Figure 4A is a Scanning Electron Microscope (SEM) image of CCP-30, which shows the calcium silicate hydrate (CSH) porous structure (average pore size of 1 μm) and surface-bound nanoparticles (average diameter of 350 nm).
[0025] Figure 4B Shows the uniform interface between the cured paste of the cementitious cooling coating and the cement-fiber substrate.
[0026] FIG. 5A to FIG. 5C yes Figure 4A Illustration of the optical performance of CCP-30. Figure 5A The solar reflectance spectra of CCP-30 in dry state and wet state (water-wet) are shown. Figure 5B The Mie scattering efficiency of nanoparticles with different diameters in the solar range is shown. Particles with a diameter of about 350 nm exhibit the broadest (300 nm to 1500 nm) scattering performance in the higher solar range. Figure 5C is a graph showing the change in scattering efficiency of a porous structure (D=1 μm) in a wet state (water) and a dry state.
[0027] Figure 5D is a graph showing the change in scattering efficiency of nanoparticles (D = 350 μm) in wet (water) and dry states.
[0028] Figure 5E is a graph showing the drop in solar reflectance of CCP-30 over the range of water absorption when wetted, which only accounts for about 2.5% of the total solar energy.
[0029] Fig. 5F is a graph showing the change of total solar reflectance in dry and wet states with increasing doping ratio. Nanoparticle doping increases both dry and wet reflectance, while the larger rising slope in the wet state corresponds to the theoretical scattering performance, i.e., sufficient nanoparticle occupancy results in less scattering drop when water is filled.
[0030] Figure 5G is a graph showing the emissivity spectrum within the atmospheric window, which indicates the good radiative cooling characteristics of CCP-30, which are partially contributed by the additive.
[0031] Figure 5H Figure 2 is an SEM image of pure CSH matrix without PVA additive and a SEM image of CSH matrix with PVA additive. The obvious morphological difference indicates that PVA is coated on the outside of CSH matrix, which leads to higher structural integrity. The simultaneous coating during hydration leads to the formation of a strong hydrogen bonding network, which helps to maintain sustainable water for cement particles to generate a well-connected CSH matrix.
[0032] Figure 6 is a schematic diagram of a cementitious cooling coating applied to a portion of the surface of a brick, wherein the brick is placed on concrete.
[0033] Figure 7A and Figure 7BThe temperature difference of the brick with the part covered with cementitious cooling paint under outdoor conditions (about 800W / m 2 sunlight intensity; relative humidity of about 65%; T of about 35°C air FIG. 7A is an optical image of a cementitious cooling coating 602 on a portion of a concrete tile 604. FIG. Figure 7B is an infrared image showing the temperature difference between the portion of brick 604 and brick 602 covered with cementitious cooling paint under direct sunlight.
[0034] Fig. 8A , Figure 8B and Figure 8C are graphs and related spectra showing the optical characteristics of multiple samples used for small-scale cooling tests. Fig. 8A is a graph showing the total solar reflectance and atmospheric window range thermal emissivity for the three samples. It should be noted that CCP-30 has a small amount of reflectance change when wetted, with error bars taken to show the range. It should be noted that CCP-30 has a similar thermal emittance to BaSO4 radiative cooler (BSRCP), while the solar reflectance is about 4% lower. The lower temperatures as well as the lower solar reflectance demonstrate the effectiveness of the evaporative cooling feature achieved by the designed structure. Figure 8B Solar reflectance spectra of three samples are shown. Figure 8C Thermal emission spectra of three samples are shown.
[0035] Fig. 9 is a graph showing typical cloudy day cooling performance of different samples, where the recording starts from a static state. The temperature curve shows that CCP-30 exhibits the best sub-ambient cooling performance, where evaporative cooling contributes to the slower heating in sunlight.
[0036] Fig.10 is a graph showing typical sunny day cooling performance of different samples. Once placed in the sun, CCP-30 exhibits a stable temperature and exhibits the slowest temperature rise in the morning rising sun, which is contributed by the evaporation of internal water.
[0037] Fig.11 (a) The results of cooling tests conducted in California; (b) The results of cooling tests conducted in Changchun. The stable cooling performance in different climates shows the wide applicability of CCP-30.
[0038] FIG. 12A shows optical images of three demonstration houses with different paints, namely, cementitious cooling paint (CCP), commercial-radiative cooler (RC) paint (CRCP), and normal white paint (NWP).
[0039] 12B is a graph showing the long-term cooling performance of different coatings for a demonstration house, where the delay in temperature peaks stems from the insulating effect of the building materials.
[0040] Fig. 12C is an infrared image showing comparative surface temperatures around 4pm, where the surface of CCP-30 is approximately 2°C cooler than the other coatings, as indicated. The infrared camera was calibrated indoors based on the surface temperature of CCP-30 prior to imaging.
[0041] Fig.13A The optical images are of three habitable-size concrete houses where electricity conservation tests were conducted, where commercial white paint, commercial radiant cooling paint, and CCP-30 were applied for comparison. The same series of air conditioning systems and independent electricity meters were installed in the houses. The target room temperature was set to 26°C, and each test lasted for 3 days.
[0042] Fig. 13B Shows 3 days of electricity consumption data recorded by an electric meter under different weather conditions.
[0043] Fig.14 The results show that different concrete bricks made under direct sunlight (about 1000W / m 2 ) at 40 °C. The image was taken after stabilization for 2 hours.
[0044] Fig.15 A and Fig.15 B is a graph showing the temperature profiles of different samples of concrete, obtained during a day of weak sunlight. Fig.15 A is a graph showing recorded temperatures for different samples. Fig.15 B is a diagram showing corresponding environmental conditions including solar intensity (solarintensity) and relative humidity (RH).
[0045] Fig.16 A and Fig.16 B is a diagram showing the temperature profiles of different samples of concrete obtained in the tests during the day. Fig.16 A is a graph showing the recorded temperatures of different samples. Fig.16B is a graph showing corresponding environmental conditions including sunlight intensity and relative humidity (RH).
[0046] Fig.17A and Fig. 17B is a graph showing results obtained from a weather acceleration robustness test. Fig.17A is a diagram showing programmed chamber conditions for two cycles. Fig. 17B is a graph showing solar reflectance before and after a 50-cycle test.
[0047] Fig.18 is a graph showing the results of a wear test (1.25 kg load, using H-10 abrasive) conducted between CCP-30 and CB. The results demonstrate that the water-absorbing polymer (PVA) and the water-collecting material (LiCl) ensure the formation of a stronger CSH matrix.
[0048] Fig.19 Schematic diagram of the compact cement powder distribution in CCP-30 paste due to the lower effective water to cement ratio (W / C). Image (a) shows the initial pure cement 191 in powder form with larger spacing 192. Image (b) shows the hydrated CS-H 193 with a weaker CSH matrix after full hydration 194. Image (c) shows the initial CCP 195 in powder form with smaller spacing 196 and BaSO4 nanoparticles 197. Image (d) shows the hydrated CSH of CCP 198 with a stronger CSH matrix after partial hydration 199.
[0049] Fig. 20 Schematic diagram of the mechanism of structural differences caused by water evaporation. Image (a) shows cement-BaSO4 paint (CB) with cracks 201, plastic shrinkage 202, and rapid water loss 203 after water evaporation. Image (b) shows CCP with uniform structure 204, negligible plastic shrinkage 205, and slower water loss 206 after water evaporation.
[0050] Fig.21 Raman spectra of CB-30 and CCP-30 are shown, confirming the formation of the CSH matrix and the different hydration states.
[0051] Fig. 22Schematic diagram of the mechanism of CSH matrix differences affected by additive-induced changes in water evaporation rate. Image (a) shows the initial condition of cement powder containing water and BaSO4 nanoparticles 221. Image (b) shows cement powder cured with a polymer additive (CCP-30). The image shows water channels 222, a stronger CSH network 223, and slower water loss 224; and image (c) shows cement powder cured without additive (CB). The image shows a weaker CSH network 225 and faster water loss 226.
[0052] Fig.23 Transmission Electron Microscope (TEM) images and associated spotting EDS elemental spectra are shown, which show a more uniform matrix in CCP-30 at the same curing time, which corresponds to different hydration states as indicated by the relative Ca / Si ratios.
[0053] Fig.24 TEM images and associated EDS spot spectra on the particle surface in CB and CCP-30 samples are shown.
[0054] Fig.25 Optical images of CCP-30 are shown on a commercial oil-based wall sealant surface 251, a water-based wall sealant surface 252, and a concrete surface 253. Good adhesion to the sealant ensures a wide range of potential applications in the construction field.
[0055] Fig.26 is a graph showing the results of the optical performance of CCP-30 obtained under a 500-hour (50-cycle) weather acceleration test. The results show that CCP-30 has good anti-degradation characteristics.
[0056] Fig. 27 : is a graph showing the optical performance comparison of CCP-30 and commercial-RC under 3 months outdoor exposure test. Commercial-RC shows a significant decline in the daylight range, while CCP-30 remains stable, indicating its excellent weather resistance and anti-pollution characteristics.
[0057] Fig.28 is a graph showing the effect of powder mixing order on optical properties. The comparable optical properties of different orders ensure that the generally accepted all-in-one method is applicable to the manufacture of CCP-30 slurries.
[0058] Fig.29is a graph showing the color rendering comparison between CCP-30 and commercial RC for visual evaluation. With comparable visible light reflectance and color rendering factors (x and y), CCP-30 presents a darker surface that is beneficial for visual comfort in sunlight.
[0059] Fig.30 is a graph showing the results of a standardized corrosion test of CCP-30 on bare reinforced concrete (R-Con). The results demonstrate the suitability of CCP-30 for bare structures.
[0060] Fig.31A and Fig.31B The color rendering characteristics of CP-30 and publicly used commercial radiant cooling paint are shown. Fig.31A The L*a*b space color rendering factors are shown, which show that CCP-30 has weaker brightness characteristics, but has comparable color preference. Fig.31B The results of the whiteness test are shown. The results show that CCP-30 presents a darker surface than the commercial reflective coating. DETAILED DESCRIPTION
[0061] The following detailed description is made with reference to the accompanying drawings, which show details and embodiments of the present disclosure for illustrative purposes. Features described in the context of one embodiment may be correspondingly applicable to the same or similar features in other embodiments, even if not explicitly described in these other embodiments. Application and / or combination and / or substitution described for features in the context of one embodiment may be correspondingly applicable to the same or similar features in other embodiments.
[0062] In the context of various embodiments, the articles “a,” “an,” and “the” used with respect to features or elements include reference to one or more features or elements.
[0063] In the context of various embodiments, the terms "about" or "approximately" as applied to numerical values encompass the exact value and a reasonable difference, such as within 10% of the specified value, as commonly understood in the relevant technical field.
[0064] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0065] As used herein, "comprising" means including but not limited to whatever follows the word "comprising." Thus, the use of the term "comprising" indicates that the listed elements are required or mandatory, but other elements are optional and may or may not be present.
[0066] As used herein, “consisting of” means including and limited to what is between the phrase “consisting of.” Thus, the use of the phrase “consisting of” indicates that the listed elements are required or mandatory, and that no other elements are present.
[0067] Specific implementations of various embodiments will be described below with reference to the accompanying drawings.
[0068] The present disclosure relates to a cementitious cooling paint and a cementitious cooling building material. Both the cementitious cooling paint and the cementitious cooling building material present a dual passive cooling mode including radiation cooling and evaporative cooling. At night, the cementitious cooling paint and the cementitious cooling building material automatically collect water vapor from the surrounding air, and store the water vapor in the concrete structure of the building or the porous structure of the cooling building material, respectively, to complete the water replenishment process. During the day, the stored water evaporates under strong sunlight to achieve evaporative cooling. When the cementitious cooling paint is directly applied to the surface of the building, or when the cementitious cooling building material of the present disclosure is used to build a building, these methods significantly enhance the passive cooling capacity of the building. In addition, commercial cement materials such as Portland cement or geopolymer cement having physical and chemical properties similar to commercial concrete are used to manufacture cementitious cooling paint and cementitious cooling building materials, and therefore the cementitious cooling paint and cementitious cooling building materials have strong adhesion to the building surface and the primer coating.
[0069] In one aspect, the present disclosure provides a cementitious cooling coating, which comprises composite cement, structural filler, water-absorbing polymer, water collecting material and water. The water and composite cement are in a predetermined ratio to form a slurry with a suitable viscosity, depending on the method of applying the cementitious cooling coating to a suitable surface.
[0070] In some embodiments, the mass ratio of water to composite cement is 0.4 to 1.2.
[0071] In some embodiments, the mass ratio of composite cement to structural filler is 0.4 to 0.7.
[0072] In some embodiments, the mass ratio of composite cement to water absorbing polymer is 0.01 to 0.03.
[0073] In some embodiments, the mass ratio of composite cement to water collection material is 0.05 to 0.3, in other embodiments, the ratio is in the range of 0.05 to 0.2, and in other embodiments, the ratio is in the range of 0.1 to 0.3.
[0074] In some embodiments, the composite cement is at least one cement selected from different types and grades of Portland cement and geopolymeric cement.
[0075] In some embodiments, the structural filler is at least one material selected from the group consisting of silicon dioxide (SiO2), barium sulfate (BaSO4), calcium carbonate (CaCO3), zinc oxide (ZnO), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), iron (III) oxide (Fe2O3), hydrated goethite (α-FeOOH), Prussian Blue, and other solar reflective nanomaterials. The structural filler comprises nanoparticles having an average particle size ranging from 0.3 μm to 2 μm, depending on the specific optical requirements.
[0076] In some embodiments, the water-absorbing polymer is at least one material selected from the group consisting of sodium poly(acrylate), sodium carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, hydroxypropyl methylcellulose, carboxymethyl cellulose, and other hydrated polymer materials for storing water.
[0077] In some embodiments, the water collection material is at least one material selected from the group consisting of deliquescent salts such as lithium chloride (LiCl) and calcium chloride (CaCl2) and hygroscopic polymer materials. The water collection material is embedded for efficient hydration at night when humidity is high and ambient air temperature is low (no sunlight).
[0078] In some embodiments, the cementitious cooling paint further comprises a dispersant. The dispersant is at least one material selected from the group consisting of sodium polyacrylic and superplasticizers such as sulfonated naphthaleneformaldehyde condensate, sulfonated melamineformaldehyde condensate, acetone formaldehyde condensate and polycarboxylates ether. In some embodiments, the superplasticizer is used to reduce the water demand of concrete. The superplasticizer can be applied to the cementitious cooling paint during the manufacturing process, or the superplasticizer can be applied before use and mixed with the cementitious cooling paint.
[0079] In some embodiments, the mass ratio of the composite cement to the dispersant is 20 to 50. In some embodiments, the cementitious cooling coating is provided in a slurry form or a semi-fluid form for use as a cooling coating to be applied to a suitable surface. In other embodiments, the cementitious cooling coating can be provided in a liquid, powder or gas form for further processing into a suitable form to be used as a coating to be applied to a suitable surface.
[0080] Figure 1 Schematic diagram of different components contained in cementitious cooling paint. Composite cement matrix 102 provides mechanical robustness and stable porous structure, and structural filler 104 of nanomaterials occupies space in the porous structure for efficient light scattering, and thus achieves an increase in reflectivity and enhances the mechanical strength of cementitious cooling paint. The porous structure allows water vapor to diffuse in the composite cement matrix 102 to be absorbed by the water collection material 106, and then absorbed by the highly hydrated water-absorbing polymer matrix 108 for storage. The water-absorbing polymer matrix acts as a micro water container in the porous structure for a lasting cooling effect. In addition, the structural filler 104 has a strong thermal emissivity in the atmospheric window, thereby providing efficient radiative cooling. By determining the proportions of the multiple components contained in the cementitious cooling paint, the cementitious cooling paint and the building materials covered with the cementitious cooling paint exhibit high mechanical robustness, sufficient water absorption characteristics at night, efficient water evaporation characteristics under sunlight, suitable sunlight reflectivity (about 85%), and sustainable passive cooling characteristics.
[0081] Figure 2 The arrangement of a layer of cementitious cooling paint 200 applied on a building surface 202 is shown. Arrow 204 indicates the direction of heat conduction within the building surface 202, and arrow 206 indicates the direction of long-wavelength infrared (LWIR) radiation. At night 208, the ambient temperature and thermal radiation decrease, while humidity increases. The water collection material absorbs water 210 from the ambient air. At this time, the evaporation amount is much less than the absorption amount, which results in water storage in the concrete matrix of the building surface 202. During the day 212, strong sunlight and high ambient temperature 214 continue to stimulate water evaporation 216, while the water absorption rate gradually decreases or becomes negligible, which results in the realization of cooling performance. At the same time, the strong thermal radiation through the atmospheric window continues to radiate energy into the air of the external environment, and thus passive radiation cooling is achieved.
[0082] The cementitious cooling coating of the present disclosure has two possible ways to collect moisture from the ambient air: (i) by water absorption; and (ii) by capillary diffusion.
[0083] Figure 3A The water collection capability of the cured cementitious cooling coating is shown. The porous structure can store water by capillary diffusion under simulated rainfall conditions, which results in about 30% by weight of the internal water storage being used for evaporative cooling, while water vapor collected from the air under real nighttime conditions results in about 15% water storage (about 27°C, 75% relative humidity). In addition to the water collection feature, it should be emphasized that the negligible swelling feature allows for a stable cycle of the absorption-desorption process. This is most important for structural purposes, and due to the stable CSH gel matrix, the cured cementitious cooling coating is able to maintain the porous structure within the composite cement matrix during the cycle, which is promising for long-term use.
[0084] Figure 3B The TGA curve shown is Figure 3A The water accumulation results shown are well consistent, indicating that the cured cementitious cooling coating can store about 30% by weight of water internally for evaporative cooling. In addition, compared with common, water-rich materials such as hydrogels, cementitious cooling coatings exhibit excellent thermal stability at extreme temperatures. This broadens the application potential of cementitious cooling coatings. In addition, micron-scale CT scans show that the cured cementitious cooling coating has a rich porous structure with an estimated pore volume of about 38% by volume. This is well consistent with the water volume evaluated by the sorbing-drying test. Figure 3C The results shown indicate that a high porosity was achieved in the strong matrix formed by the coating type slurry. In addition, the evaporation characteristics between pure water and the soaked cementitious cooling coating were compared and the results are shown in Figure 2. Figure 3D As shown in Figure 2, unlike the sharp peak obtained from pure water, the water in the cementitious cooling paint has a smooth endothermic curve starting from a lower temperature. This indicates a favorable heat dissipation feature contributed by the porous structure within the normal air temperature range.
[0085] In various embodiments, the cementitious cooling coating is manufactured by mixing composite cement, structural filler, water-absorbing polymer, water-collecting material, dispersant and water in appropriate proportions. The mixing can be performed in any order depending on the application. In some embodiments, the water-absorbing polymer, water-collecting material and water are premixed in liquid form, while the composite cement and structural filler are premixed in solid form. The liquid mixture and the solid mixture are then uniformly mixed to form a cementitious cooling coating precursor or a cementitious cooling coating, depending on the amount of water used in the process of manufacturing the cementitious cooling coating. In some embodiments, the cementitious cooling coating precursor is further mixed with water and / or a dispersant in an appropriate amount and blended to form a slurry with a higher viscosity suitable for use as a coating. The amount of different components in the cementitious cooling coating allows the formation of a slurry with a higher viscosity, and this makes the slurry easy to apply to suitable surfaces and materials, including application to the side walls of the building at the desired thickness. The strong adhesion between the cementitious cooling coating and commercial concrete leads to the formation of a calcium silicate hydrate (CSH) gel interface. This results in a superior adhesion of the cementitious cooling coating to the concrete surface to which it is applied. The slurry exhibits a rapid setting / hardening characteristic, which protects it from potential damage during the curing process.
[0086] According to a second aspect, the present disclosure provides a cementitious cooling building material. The cementitious cooling building material comprises composite cement; structural filler; water-absorbing polymer; water-collecting material; dispersant and water; wherein the mass ratio of water to composite cement is 0.5 to 1.5; the mass ratio of composite cement to structural filler is 0.4 to 0.7; the mass ratio of composite cement to water-absorbing polymer is 0.01 to 0.03; the mass ratio of composite cement to water-collecting material is 0.05 to 0.3; and the mass ratio of composite cement to dispersant is 8 to 15.
[0087] The cementitious cooling building material further comprises alkaline water for hydrating the cementitious cooling building material and preventing the cementitious cooling building material from cracking.
[0088] In some embodiments, the composite cement is at least one cement selected from different types and grades of Portland cement and geopolymeric cement.
[0089] In some embodiments, the structural filler is at least one material selected from the group consisting of silicon dioxide (SiO2), barium sulfate (BaSO4), calcium carbonate (CaCO3), zinc oxide (ZnO), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), iron (III) oxide (Fe2O3), hydrated goethite (α-FeOOH), Prussian Blue, and other solar reflective nanomaterials. Depending on specific optical requirements, the structural filler comprises nanoparticles having an average particle size in the range of 0.3 μm to 2 μm.
[0090] In some embodiments, the water-absorbing polymer is at least one material selected from the group consisting of sodium poly(acrylate), sodium carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, hydroxypropyl methylcellulose, carboxymethyl cellulose, and other hydrated polymer materials for storing water.
[0091] In some embodiments, the water collecting material is at least one material selected from the group consisting of deliquescent salts such as lithium chloride (LiCl) and calcium chloride (CaCl2) and hygroscopic polymer materials. The water collecting material is embedded to efficiently replenish water at night when humidity is high and ambient air temperature is low (no daylight).
[0092] In some embodiments, the dispersant is at least one material selected from the group consisting of sodium polyacrylic and superplasticizers such as sulfonated naphthalene formaldehyde condensate, sulfonated melamine formaldehyde condensate, acetoneformaldehyde condensate, and polycarboxylates ether. In some embodiments, the superplasticizer is used to reduce the water demand of concrete. The superplasticizer can be applied to the cementitious cooling building material during the manufacturing process, or the superplasticizer can be applied and mixed with the cementitious cooling building material before use.
[0093] In some embodiments, the cementitious cooling building material has a viscosity suitable for manufacturing cement-based building products, including but not limited to cooling tiles, cooling bricks, cooling concrete, cooling concrete blocks, cooling concrete panels, and cooling cement walls.
[0094] In some embodiments, cementitious cooling building materials are manufactured in a manner similar to cementitious cooling coatings, except that, in order to use cementitious cooling building materials for manufacturing cement-based building products, the cementitious precursor in the form of a slurry is hydrated before the slurry is used to be molded into a shape suitable for manufacturing cement-based building products. In some embodiments, the cementitious precursor is hydrated by intermittently spraying alkaline water to maintain the higher mechanical strength in the cementitious cooling building materials and prevent cracks from being generated in the cementitious cooling building materials. In some embodiments, alkaline water is sprayed once every 1 to 2 days, and the amount of spraying is sufficient to keep the cementitious cooling building materials fully hydrated before and during the molding process. In some embodiments, the cementitious precursor of the building material used to manufacture cement-based building products has a lower viscosity than the cementitious cooling coating precursor to promote the easier flow of the cementitious precursor during the molding process. Any suitable molding process and conditions can be used to manufacture cement-based building products using cementitious cooling building materials without departing from the scope of the present disclosure.
[0095] According to a third aspect, the present disclosure provides a cement-based building product comprising the cementitious cooling building material of the present disclosure. In some embodiments, the cement-based building product is selected from one of cooling tiles, cooling bricks, cooling concrete, cooling concrete blocks, cooling concrete panels and cooling cement walls.
[0096] According to a fourth aspect, the present disclosure provides a set of components containing the cementitious cooling coating of the present disclosure as defined above. The set of components comprises a first part, the first part comprising a solid mixture consisting of composite cement and structural filler; and a second part, the second part comprising a liquid mixture consisting of water-absorbing polymer, water-collecting material, dispersant and water; wherein the mass ratio of water to composite cement is 0.4 to 1.2; the mass ratio of composite cement to structural filler is 0.4 to 0.7; the mass ratio of composite cement to water-absorbing polymer is 0.01 to 0.03; the mass ratio of composite cement to water-collecting material is 0.05 to 0.3; and the mass ratio of composite cement to dispersant is 20 to 50.
[0097] In some embodiments, the cementitious cooling coating in the kit is manufactured by mixing the first part containing the solid mixture and the second part containing the liquid mixture together and blending the two parts to obtain the cementitious cooling coating. In other embodiments, the cementitious cooling coating is manufactured by mixing the first part containing the solid mixture and the second part containing the liquid mixture with a predetermined amount of water and blending the mixture to obtain the cementitious cooling coating with a suitable viscosity, so that the cementitious cooling coating can be applied to a suitable surface.
[0098] According to another aspect, the present disclosure provides a method for manufacturing a cement-based building product comprising the cementitious cooling building material of the present disclosure. The method includes mixing composite cement with structural fillers to manufacture a solid mixture; mixing a water-absorbing polymer with a water-collecting material, a dispersant, and water to manufacture a liquid mixture; uniformly mixing the solid mixture with the liquid mixture to form a cementitious cooling building material precursor; hydrating the cementitious cooling building material precursor using alkaline water to prevent cracking of the cementitious cooling building material precursor; and molding the hydrated cementitious cooling building material precursor into a desired cement-based building product. In some embodiments, the mass ratio of water to composite cement is 0.5 to 1.5; the mass ratio of composite cement to structural fillers is 0.4 to 0.7; the mass ratio of composite cement to water-absorbing polymer is 0.01 to 0.03; the mass ratio of composite cement to water-collecting material is 0.05 to 0.3; and the mass ratio of composite cement to dispersant is 8 to 15.
[0099] In some embodiments, the cementitious cooling building material precursor is intermittently hydrated in sufficient amounts, which is sufficient to keep the cementitious cooling building material fully hydrated before and during the molding process. In some embodiments, alkaline water is sprayed once every 1 to 2 days. Other frequencies can be adopted without departing from the scope of the present disclosure. Any suitable molding process and conditions can be adopted to manufacture cement-based building products using cementitious cooling building materials without departing from the scope of the present disclosure. In some embodiments, the cement-based building product is selected from one of cooling tiles, cooling bricks, cooling concrete, cooling concrete blocks, cooling concrete panels and cooling cement walls.
[0100] The cementitious cooling coating of the present disclosure presents several advantages. First, due to the presence of water in the layer, the cementitious cooling coating is an efficient thermal insulation layer because the cementitious cooling coating has the ability to absorb water vapor from the surrounding air. Second, the cementitious cooling coating is a combination of a radiative cooling material that operates by thermal radiation (within the atmospheric window) and an evaporative cooling material that operates by water evaporation. Third, the cementitious cooling coating has a low solar reflectance, which can avoid light pollution, which is a disadvantage of neutral white radiative cooling materials. The cementitious cooling coating can provide a cooling effect even when applied to the side walls of outdoor surfaces and indoor surfaces. This is not possible for some cooling coatings known in the prior art, and the cooling effect of these cooling coatings on the side walls is weakened due to insufficient radiation angle. When the cementitious cooling coating of the present disclosure is applied to the surface, the cementitious cooling coating allows thickness control. The cementitious cooling coating has strong adhesion and can be cured quickly. Building materials covered with cementitious cooling coatings are exposed to strong sunlight (about 800W / m 2 ) under the conditions of high temperature, the temperature is up to 12°C lower than that of conventional building materials, which indicates its significant cooling effect.
[0101] Cementitious cooling paint and cementitious cooling building materials are cement-based composites that meet industrial requirements and are cost-effective. Cementitious cooling paint can be manufactured by simply mixing the components to form a cementitious cooling paint, by mixing the cementitious cooling paint with water and / or a superplasticizer additive, or by mixing a solid mixture and a liquid mixture with water to form a cementitious cooling paint. Similarly, cementitious cooling building materials can be manufactured by simply mixing the components to form a cementitious cooling building material, by mixing the cementitious cooling building material with water to obtain a desired viscosity, or by mixing a solid mixture and a liquid mixture with water to form a cementitious cooling building material, so as to be used in the manufacture of other cement-based building products. Simple manufacturing steps based on common commercial materials make it cost-effective and environmentally friendly, and have excellent scalability.
[0102] Cementitious cooling paint can be applied to building materials such as tiles, bricks, concrete, concrete blocks, concrete slabs, cement walls, etc. for use in the construction industry. Cementitious cooling paint can be applied to the construction of roofs for passive cooling and insulation purposes. Cementitious cooling paint can provide a medium reflective coating for the purpose of cooling the side walls. Cementitious cooling paint can be applied to concrete walls for the purpose of repair and reinforcement. Cementitious cooling paint can also be used as other outdoor cooling coverings, such as water tank coverings and cold chain vehicle coatings. Cementitious cooling paint can also be used as marine coatings to avoid heating and energy consumption. Cementitious cooling building materials can be used to manufacture cement-based building products with cooling effects, including but not limited to cooling tiles, cooling bricks, cooling concrete blocks, cooling concrete slabs, cooling cement walls and cooling concrete as pavement materials.
[0103] In order to facilitate a better understanding of the present invention, the following examples of specific embodiments are given. The following examples should not be considered as limiting or defining the entire scope of the present invention. Those skilled in the art will recognize that the examples listed below are not an exhaustive list of embodiments of the present invention.
[0104] Example
[0105] Material
[0106] The raw materials of the cooling paint samples included white cement (AALBORG 52.5N), polyvinyl alcohol (molecular weight about 13,000, Sigma Aldrich), BaSO4 nanoparticles (A22 industrial products, Hico Novel Materials) and lithium chloride (Sigma Aldrich). All materials were used directly after purchase without further treatment.
[0107] Example 1 - Manufacturing of cementitious cooling paint and other comparative examples
[0108] First, a 10% by weight polyvinyl alcohol (PVA) solution was prepared by dissolving polyvinyl alcohol (PVA) powder in deionized water at 60° C. Three types of materials were prepared in this example, namely cementitious cooling paint (CCP), cement-BaSO4 paint (CB) and pure cement.
[0109] A cementitious cooling paint (CCP) precursor containing cement (10 g), barium sulfate (BaSO4) (10 g to 30 g), 10 wt% PVA (5 ml), lithium chloride (LiCl) (1 g) and deionized water (15 ml) was manufactured. The sample was named CCP-30, CCP-30 refers to CCP containing 30 g of BaSO4.
[0110] Before manufacturing, 1 g of LiCl was dissolved in 5 ml of room temperature deionized water to avoid clustering effect, thereby forming solution A. Cement powder and BaSO4 were evenly mixed in a 250 ml beaker to break up the agglomerates formed during storage. Then, 15 ml of 10% mass percent PVA solution was slowly poured into the mixed powder and stirred continuously. After 5 minutes of stirring, 5 ml of solution A was applied and stirred continuously for another 10 minutes.
[0111] A CB sample containing cement, BaSO4, LiCl and deionized water was manufactured. The sample was named CB-30, which refers to CB containing 30 grams of BaSO4. The precursor preparation of CB was the same as that of CCP, except that the application of 15 ml of 10% by mass PVA solution was replaced by 15 ml of deionized water.
[0112] Pure cement samples containing only cement and deionized water were manufactured. After mixing cement powder with water, the solution was placed in a silicone mold for curing.
[0113] Example 2 - Manufacturing of cementitious cooling building materials
[0114] The cementitious cooling building material was manufactured by premixing cement powder with BaSO4 to form a solid mixture, and premixing 10% by mass of PVA with LiCl (1 g), deionized water (15 ml) and a dispersant to form a liquid mixture. The liquid mixture was then uniformly mixed with the solid mixture to produce a cementitious cooling building material in the form of a slurry.
[0115] To manufacture cement-based building products, slurry with a desired viscosity is hydrated before feeding it into a mold and during molding. During the hydration process, alkaline water is sprayed frequently (once / 1 to 2 days) to maintain high mechanical strength and avoid cracking in cementitious cooling building materials.
[0116] Example 3
[0117] Figure 4ASEM (Scanning Electron Microscope) images of CCP-30 manufactured from Example 1 are shown. The SEM image shows a CSH porous structure with an average pore diameter of about 1 μm and surface-bound nanoparticles with an average diameter of 350 nm. CCP-30 exhibits a spontaneously and uniformly formed porous structure due to the in-situ reaction of the cementitious material with water. It is clearly shown that the additives are fixed to the porous walls through strong chemical bonds, which allows for efficient water storage within the porous structure. Having properties similar to those of building materials, CCP-30 forms a uniform interface with commercial cementitious substrates, which results in strong adhesion that enhances its initial robustness (see Figure 4B Based on optical property engineering, the inventors succeeded in giving cementitious cooling coatings a higher solar reflectivity by penetrating nanoparticles of selected size (in the range of about 300nm to 400nm) (see Figure 5A ), which blocks most of the direct solar heating effect through strong Mie scattering.
[0118] The scattering efficiency at the hole / air / water interface and the particle / air / water interface was evaluated by finite-difference time-domain (FDTD) simulations. Standard optical indices (n. k) for multiple components were applied. The scattering cross sections of multiple objects (surrounded by air / water) were calculated and considered as the scattering efficiency after dividing by the cross section length under total-field scattered-field (TFSF) and perfect matching layer (PML) boundary conditions.
[0119] Figure 5B The selected barium sulfate (BaSO4) is shown to have a strong Mie scattering effect (darker shades) in the range of 300nm to 1500nm, where about 90% of the solar energy is in the range of 300nm to 1500nm. Particles with a diameter of about 350nm exhibit the broadest scattering efficiency along the solar spectrum, where its strong scattering effect is mainly located in the higher solar bands (300nm to 1500nm accounts for more than 90% of the solar energy), which indicates its suitability as a solar light scattering medium.
[0120] Barium sulfate (BaSO4) exhibits negligible absorption in the UV range, which blocks an additional 4% of solar heating and achieves UV protection. Not only the nanoparticles, but also the porous structure of CCP contributes to the solar reflectance in the dry state, where strong Mie scattering occurs at the boundaries due to comparable wavelength pore size and the difference in refractive index between the matrix and air ( Figure 5C ). Through cooperative scattering from pores and nanoparticles, CCP has a solar reflectance of about 93% in the dry state ( Figure 5A ).
[0121] It has been reported that the reflectivity of porous structures decreases by filling with liquids, where the minimally reduced refractive index at the pore boundaries leads to weaker scattering effects. Figure 5C As shown in Figure 2, the scattering efficiency of the CCP porous structure decreases sharply upon wetting, and at the same time, it is similar to the previously reported reversible porous structure ( Figure 5A ), the overall daylight reflectance in the non-aqueous absorption range (300nm to 1300nm) remains very high compared to the 2.5 nm range. The stable optical performance originates from the Mie scattering of the nanoparticles, which exhibit comparable scattering efficiency in water and air ( Figure 5D ). Since the nanoparticles are attached to the porous matrix, the increased doping level can lead to a larger surface area, resulting in minimized scattering changes. Since the CSH matrix provides mechanical stability as a skeleton, excessive application of nanoparticles will lead to weaker matrix connections, resulting in poor mechanical properties. The results show that CCP-30 only exhibits less than 2% optical changes in the non-aqueous absorption range, while maintaining good mechanical properties. Although minimized pore scattering and water's inherent near-infrared absorbance lead to reduced reflectivity from 1300nm to 2500nm ( Figure 5E ), taking into account the energy distribution, only less than 3% of the solar energy is introduced. Therefore, the porous CCP-30 exhibits ultra-low optical changes (less than 5%, Fig. 5F ), while maintaining a strong structure during water circulation, which is a successful solution to the contradiction between optical performance and water accumulation in a single porous panel. At the same time, CCP-30 exhibits a long-wave infrared emissivity of about 94% contributed by the intrinsic vibration of -SO4 and -OH, which is significantly higher than that of the coating without additives ( Figure 5G ), and originates from the coating of the polymer on the substrate surface ( Figure 5H ).
[0122] Example 4
[0123] Figure 6Schematic test conditions of the manufactured samples for side wall application are shown. Cementitious cooling paint 602 is evenly applied on half of the surface of concrete brick 604, which is placed on concrete block 606 and directly exposed to strong sunlight in direction 608 for temperature monitoring.
[0124] Field tests were conducted using a calibrated infrared camera to monitor near-static state temperature differences. FIG7A shows an optical image of the manufactured sample, where there is a clear color difference between the ordinary brick and the portion of the brick covered with the cementitious cooling coating of the present disclosure. The color of the cementitious cooling coating is white, and this is reasonably designed so that it has a high solar reflectance (about 85%), but not too white to cause light pollution under direct sunlight. This feature is suitable for application on the side walls of buildings. Figure 7B The infrared image shown clearly shows the temperature contrast after stabilization for 2 hours under strong sunlight, where a temperature difference of -6°C was observed between the left (bare surface of the concrete brick) and right (surface of the brick covered with cooling paint) parts of the brick.
[0125] Example 5 - Cooling Performance
[0126] Outdoor tests were conducted to evaluate the cooling performance of CCP-30 samples. First, CCP-30, commercial radiant cooling materials (commercial-RC coatings: Nippon Cool-Tech ® ) and the reported high reflective BaSO4 radiative cooler (BSRCP), the optical characteristics of the three samples were Fig. 8A , Figure 8B and Figure 8C In a typical cloudy day in Singapore with a relative humidity (RH) of about 90%, CCP-30 exhibits the lowest temperature, which is about 350W / m 2 The air under sunlight is about 2.5℃ lower ( Fig. 9). Theoretical calculations demonstrate that the radiative cooling performance in Singapore during the day is dominated by solar reflectivity. The significantly lower temperature and slower temperature rise of CCP-30 compared to BaSO4 radiative cooling materials indicate the effectiveness of its evaporative cooling characteristics. Although higher RH hinders the radiative cooling capacity of both, the increase in evaporative cooling capacity induced by unsaturated vapor pressure leads to lower temperatures. Simultaneously, the slowest temperature rise at sunrise indicates effective vapor accumulation. In addition, net evaporation begins when CCP-30 has a lower temperature than other cooling materials at night, while net evaporation stops at around 7 pm, when all samples maintain the same temperature in the absence of sunlight. This indicates a day-long evaporation duration in cloudy weather. The comparable temperatures at night (before and after net evaporation starts) indicate negligible heating effects caused by the hygroscopic process. Due to the negligible expansion properties of the solid porous matrix of the cementitious cooling coating, slow hygroscopicity can be applied without worrying about structural changes during the wetting / drying process, thus preventing unnecessary adhesion issues. Similarly, CCP-30 presents its lowest temperature during the rising sunlight period (around 10am) and remains about 3°C cooler than the air after the longer night period ( Fig.10 ). The better cooling performance can be attributed to the evaporative cooling feature compared to the coating with higher reflectivity. It is worth noting that the lower temperature presented by CCP-30 proves that incorporating the evaporative feature in the coating achieves better cooling performance and lower solar reflectivity, which is suitable for side wall applications where visual and thermal comfort are always the focus. Meanwhile, after the water is exhausted at around 7 pm, all cooling materials maintain the same temperature, while CCP-30 shows lower temperatures starting at 4 am ( Fig.10 This shows that net evaporation starts after the water storage process and runs for about 9 hours (until the end of the test). Outside the tropics, CCP-30 has a very good performance in different climate regions (California and Changchun, Fig.11 ) exhibits stable sub-ambient cooling performance, which indicates its broad cooling potential. In conclusion, CCP-30 serves as a good radiative cooling material, while also exhibiting the additional feature of being an evaporative cooling material, which is achieved by self-driven water circulation without mechanical deformation.
[0127] In addition to surface cooling, the reduction in indoor temperature and electricity savings can more directly evaluate the performance of cooling coatings. Long-term scalable tests were conducted on three demonstration houses built with industrial concrete blocks (size: 50 cm long: 40 cm wide: 70 cm high, wall thickness about 10 cm). Two commercial coatings [normal white paint (NWP): Seamaster White Coat-7000N ® and Commercial-RC (CRCP): Nippon Cool-Tech ® ] was coated three times to ensure optical uniformity. CCP-30 was fully coated without an additional bonding layer, which presented a matte white surface (Figure 12A). The delayed temperature peak compared to air and sunlight, caused by the heat capacity and lower thermal conductivity of the concrete block, was consistent with the monitoring of indoor temperature (Figure 12B). Obviously, the houses covered with CCP-30 always presented the lowest temperature, which was more than 4.5°C lower than the other houses and about 7°C lower than the air, indicating that CCP-30 has excellent passive cooling performance in tropical climates. In addition, the infrared image ( Fig. 12C ) compared the surface temperatures as indicated by the arrows. The average surface temperature difference between CCP-30 and the other two coatings was about 2°C, with the internal temperature difference remaining above 4°C for hours until nighttime, indicating that CCP-30 has excellent thermal resistance properties. The difference in temperature reduction between inside and outside directly indicates the effective and maximum reduction of heat accumulation by the additional evaporative cooling feature. In addition, the contrasting temperature distribution shown in the infrared images demonstrates the effectiveness of the integrated passive cooling material in façade applications.
[0128] To further verify the cooling effect, energy saving effect and weather adaptability of CCP-30, three coated, habitable-sized concrete houses with air conditioning systems and independent electricity meters were built for comparison (optical images as shown in Fig.13A). The houses had a wall thickness of about 15 cm with internal insulation, which is similar to real building codes. The target indoor temperature was set at 26°C, which is generally considered a comfortable temperature value. Two sets of 3-day tests were conducted to evaluate energy consumption under different weather conditions. During typical, alternating sunny and rainy days, CCP-30 presented energy savings of about 20% to 40% compared to commercial coatings, which was contributed by both radiative cooling and evaporative cooling. It is worth noting that CCP-30 presented a stable energy saving of about 40% during continuous rainy days compared to both CRCP and NWP. Although the similar power consumption between the two commercial coatings indicates a negligible difference in contribution between solar reflection and radiative cooling, the significant energy savings of CCP-30 mainly come from evaporative cooling, even at higher RH. In summary, CCP-30 serves as a comprehensive passive cooling material with strong adaptability to different weather conditions, which is attributed to the stable optical properties and the robust porous structure.
[0129] Example 6
[0130] Cementitious cooling building materials were evaluated in field tests. Fig.14 The device mainly has three types of samples: ordinary concrete 902; cooling concrete 904 covered with different component ratios; and high reflectivity concrete 906. The cooling concrete 904 has a suitable solar reflectivity, especially in the visible light range, which is designed to prevent light pollution. For the high reflectivity concrete 906, it backscatters most of the solar energy through the neutral white color, which leads to concerns about light pollution under strong sunlight. Fig.15 As shown, the cementitious cooling building material disclosed in the present invention has a thermal conductivity of 1000 W / m 2 Under sunlight, a significantly lower temperature is achieved, similar to that of highly reflective materials. This is attributed to the combined evaporation and radiation cooling.
[0131] Fig.15 and Fig.16 The results obtained from the field tests shown in the figure demonstrate the long-lasting cooling performance of the cementitious cooling building materials disclosed herein. During the night, the cooling concrete absorbs water from the ambient air, which should increase its temperature. In contrast, the three types of samples were close to the temperature at night (see Fig.15 ), indicating that the gradual water absorption / water collection process generates negligible heat, which is important to avoid temperature peaks. During the day, the cooling concrete exhibits a temperature 12°C lower than normal concrete and similar to highly reflective concrete without glare / light pollution issues, such as Fig.16The sustainable cooling performance during the day indicates that the cooling concrete coated with the cementitious cooling coating of the present disclosure is adequately replenished with water at night.
[0132] Example 7 - Robustness testing
[0133] For long-term outdoor cooling, sunlight degradation of coatings always causes irreversible effects, especially for products using organic binders. In this example, robustness tests are performed in an environmental exposure chamber to evaluate their optical properties. Simulated weather conditions of sunlight, rain and night are programmed, such as Fig.17A As shown, 50 cycles are set for the degradation test. Fig. 17B The results shown show that the cementitious cooling coating of the present disclosure exhibits stable optical properties, which indicates that it has excellent anti-sunlight degradation characteristics suitable for outdoor use. Abrasion tests were also conducted to demonstrate the stability of the porous structure formed. The results obtained were compared with dense commercial coatings. Fig.18 It is shown that the porous cementitious cooling coating of the present disclosure also has a relatively high robustness as indicated by the anti-wear characteristics, which is mainly attributed to the formation of the CSH gel matrix.
[0134] The CCP-30 structure arises from the hydration process between cement powder and water, where a CSH gel is formed to provide robustness. In this process, the ratio of water to cement (W / C ratio) plays an important role. Generally, the W / C ratio is positively correlated with the porosity of the CSH matrix and is usually maintained within 0.4 to 1.0 to maintain good mechanical robustness and mortar workability. While the uniform dispersion of nanoparticles leads to better optical properties, the increase of water as a reactant and dispersant is necessary, resulting in a higher W / C ratio. At the same W / C ratio (about 2), a chalking phenomenon was observed in neat cement, while CCP-30 exhibited only negligible weight loss even after severe abrasion. This is attributed to the insufficient compaction between cement powders during the reaction ( Fig.19 ), thus limiting the connection between CSH particles during hydration. This is further confirmed by the distinct boundaries of hydrated CSH, which indicates poor interconnection. Relatively speaking, BaSO4 nanoparticles form weak hydrogen bonds with surrounding water molecules ( Fig.19), which captures part of the water to reduce the effective free water ratio, which leads to compaction of the cement powder during hydration. Compared with reported results, the yield stress (YS) of the freshly prepared CCP-30 precursor shows that the effective W / C is between 0.38 and 0.47, which proves that it not only has a more compactable structure but also has appropriate workability similar to that of ordinary mortar slurries. Due to its viscoelastic properties, the thickness of CCP-30 can be adjusted (up to 2.28 mm) through a one-time coating procedure, which obtains sufficient water storage volume and potential aesthetic purposes such as patterning. However, the application of nanoparticles alone is not sufficient to obtain a strong porous structure, and cracks appear in the porous structure early in the hydration process. It is worth noting that the CCP-30 slurry continues to lose water once applied, and the cracks are mainly attributed to the plastic shrinkage caused by capillary pressure, which is determined by the water loss rate ( Fig. 20 ). In contrast, a homogeneous structure is obtained by applying about 2 wt% PVA and LiCl, where a strong hydrogen bonding network and hygroscopic effects help retain water and thus lead to negligible plastic shrinkage ( Fig. 20 ). In addition to the powdering and cracking issues, the anti-wear properties were also investigated to evaluate the surface robustness. The negligible weight loss of CCP-30 under severe wear (1.25 kg load for a wheel with H-10 roughness) over 540 cycles undoubtedly proves its strong mechanical properties. Since the robustness mainly originates from the expansion and connection of the hydrated phase, the weaker surface of CB-30 indicates a lower density of CSH connections, in other words, a lower density of CSH connections is an expression of a lower degree of hydration.
[0135] Raman spectroscopy confirmed the formation of CSH matrix in both samples. -1 The different peaks indicate the contrasting generation of calcium hydroxide, which corresponds to the lower degree of hydration in CB-30. Fig.21 The slower water loss caused by the polymer additive and the simultaneous vapor collection through hygroscopic effects enabled the cement powder (in CCP-30) to undergo a longer hydration period to achieve adequate expansion and interconnection, whereas the cement powder in the additive-free precursor (CB) encountered insufficient reactant (water) during the hydration process for several days, which resulted in poor connectivity and, therefore, a weaker matrix ( Fig. 22). It is noteworthy that the initial curing time of CCP-30 (about 2h to 3h, according to the Vicat Needle Method of C191-08) is similar to that of commercial coatings, while the subsequent longer hydration reaction continues to enhance the robustness to a higher level. At the same time, the CSH matrix in CCP-30 has a more uniform crystal structure compared to that of CB-30, with EDS results showing a contrasting Ca-Si ratio, which further indicates the difference in the degree of hydration ( Fig.23 ). It is obvious that the nanoparticles are tightly attached to the porous matrix through strong hydrogen bonding interactions, where PVA and LiCl are evenly distributed on the matrix surface ( Fig.24 ). Through the above optimization, CCP-30 presents a uniform porous structure and excellent robustness, as well as anti-swelling characteristics after spontaneous hydration.
[0136] Example 8
[0137] For large-scale application of coating products, adhesion, durability and aesthetic properties play an important role. The cement-based nature of CCP-30 determines its excellent adhesion on concrete, the most widely used building material ( Fig.25 ), where the SEM image and element distribution map show a clear interface between CCP-30 and the dense concrete substrate through Ba and S elements ( Figure 4B ). The wide distribution of Ca indicates a homogeneous interface, which can be attributed to the formation of CSH with a non-hydrated phase in the substrate. Except for the bare building surface, the re-coating project is based on a primer / sealant for protection and better adhesion. Therefore, the adhesion between CCP-30 and industrial wall sealant was evaluated. Fig.25As shown, CCP-30 adheres tightly to both the oil-based wall sealant surface 251 and the water-based wall sealant surface 252 without cracking and falling off (vertical coating) after curing, which is attributed to the abundant Si-O bonds and strong hydrogen bonding interactions. Good adhesion after 90 days of direct outdoor exposure ensures long-term stability and a wide range of surface applications. Both NWP and CCP-30 are water-based coatings. Due to the uneven morphology and less water loss in the concrete structure, NWP cracks at the edges of the two concrete blocks, while CCP-30 cures uniformly without obvious edges. This is because the faster water loss of PVC coatings leads to uneven particle dispersion and uneven binder cross-linking, resulting in strain-induced cracking. In contrast, the large amount of water fixed by the strong hydrogen bonding network (polymer induced) in CCP-30 ensures that less water is lost into the substrate, thereby maintaining a stable structure. Accordingly, CCP-30 not only exhibits good structural stability, but also exhibits the function of repairing defects on the concrete surface.
[0138] The effect of water cycles on porous structures is considered to be a major concern at present, as reported passive cooling materials are mainly based on hydrogels, which present swelling and adhesion issues. A test was conducted and the results showed that CCP-30 remained adherent after 100 water cycles without any structural changes, which eliminates the concerns about swelling and ensures that it has stable integrated passive cooling characteristics under different daily weather conditions.
[0139] Weather resistance tests were performed to evaluate the optical stability under environmental conditions. A weather simulation chamber was used to alternately repeat sunlight, rain, and darkness for approximately 50 cycles (500 hours, parameters such as Fig.17A ) to induce surface degradation, while CCP-30 exhibited negligible optical changes ( Fig.26 In addition, a 3-month outdoor exposure test was conducted (3 March 2023 to 3 June 2023, Singapore) to compare commercial RC with CCP-30 ( Fig. 27 ). The commercial RC exhibits a significantly reduced reflectivity, while CCP-30 remains stable. In fact, the UV-absorbing properties of commercial RC can cause the polymer to degrade under the synergistic effects of humid air, strong sunlight and high temperature, while the UV-resistant properties and the strong CSH matrix give CCP-30 good optical stability. In addition, the hygroscopic effect introduces a thinner water film on the CCP surface pore matrix, which minimizes the accumulation of static charges and allows the transportation-off of particles / dust.
[0140] In addition to environmental resistance, wear resistance tests were performed to evaluate the mechanical robustness of the surface. To simulate the severe wear that can occur in daily life, a harder abrasive (H-10) with a load of 1.25 kg was used. The porous CCP-30 exhibited about 70% less weight loss than the dense commercial RC after 540 cycles, which was attributed to the rigidity provided by the CSH gel, where comparative surface evidence was left.
[0141] All in all, the CCP-30's durable, sturdy construction promises long-term, stable outdoor use.
[0142] The two solid phases present contrasting sizes (cement particles 3 μm to 30 μm, nanoparticles about 350 nm) and interact differently with water. Specifically, water acts as a dispersant for the nanoparticles while reacting with the cement particles. Obvious, sequence-related side effects would lead to additional steps in the precursor fabrication, which results in higher time / cost consumption. Therefore, the effect of the order of solid phase application was investigated to further evaluate the applicability. Fig.28 As shown, the comparable reflectance for different application sequences demonstrates the feasibility of a one-step approach, which matches the standard use procedure for cementitious products.
[0143] According to the mechanism of radiative cooling, heat emission facing the sky (rooftop application) is advantageous, while the side wall setting narrows the effective incident angle into the atmospheric window and receives more energy emitted from the surrounding environment. Relatively speaking, the non-directional evaporation characteristics directly consume the incident energy at the surface and reduce the internal energy triggered by the unsaturated vapor pressure (RH less than 100%), which ensures the applicability of side wall applications. However, higher whiteness is always a problem under sunlight, which causes visual discomfort. Therefore, by comparing CCP-30 with commercial RC (Nippon Cool-Tech Radiant Heat Dissipation Coating) for public use on the facades of public residential buildings based on different standards, the side wall setting can effectively reduce the impact of radiative cooling on the environment. ® ) to comprehensively evaluate the color rendering performance of CCP-30. Fig.29 ) confirms that the dominant wavelength (x) and saturation (y) are comparable between the two coatings, while CCP-30 exhibits a lower brightness (Y). In addition, the L*a*b space (CIE 1976, Fig.31A ) showed similar results, i.e., the two coatings showed comparable colors (a* for red-green, b* for yellow-blue), but different whiteness (L* for white-black). Consistently, the lower whiteness proved that CCP-30 was darker, which can be attributed to the matte surface caused by the porous structure. Therefore, CCP-30 has a lower whiteness, but has better performance than commercial RC and high reflective radiative cooling materials (whiteness of about 94, Fig.31B), which provides inspiration for designing effective passive cooling coatings for building facades with appropriate albedo.
[0144] The corrosion induction of CCP-30 was also investigated. Since the embedded LiCl acts as a water reservoir outside of rainfall events, migration into reinforced concrete (R-Con) was considered a potential corrosion source. Corrosion was evaluated over a full month using the three-electrode method according to ASTM C876-91, where CCP-30 was directly coated on R-Con cubes and semi-immersed in water ( Fig.30 ). Obviously, a passive film was formed during the initial curing stage within the first five days, in which the open circuit potential (OCP) began to rise. After stabilization, some Cl - Co-diffusion with water into R-Con along the capillary diffusion path and leads to a decrease in OCP. It is noteworthy that a stable OCP of about -200 mV is observed, which is considered to be a safe and non-corrosive state of R-Con (ASTM C876-91 standard indicated by the dotted line), indicating its applicability for exposed buildings.
[0145] Although the embodiments of the present invention have been shown and described, the application is not limited to the embodiments. On the contrary, it will be appreciated by those skilled in the art that various modifications and changes may be made to the embodiments of the present invention without departing from the scope of the present invention, which is set forth in the claims.
Claims
1. A cementitious cooling paint, comprising: Composite cement; Structural packing; Water-absorbing polymers; Water collection materials; and water; The mass ratio of the water to the composite cement is 0.4 to 1.2; The mass ratio of the composite cement to the structural filler is 0.4 to 0.7; The mass ratio of the composite cement to the water-absorbing polymer is 0.01 to 0.03; and The mass ratio of the composite cement to the water collecting material is 0.05 to 0.
3.
2. The cementitious cooling paint according to claim 1, further comprising: Dispersant, wherein the mass ratio of the composite cement to the dispersant is 20 to 50.
3. The cementitious cooling paint according to claim 1, wherein the composite cement is at least one cement selected from the group consisting of different types and grades of Portland cement and geopolymer cement.
4. The cementitious cooling paint according to claim 1, wherein the structural filler is at least one material selected from the group consisting of silicon dioxide (SiO2), barium sulfate (BaSO4), calcium carbonate (CaCO3), zinc oxide (ZnO), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), iron (III) oxide (Fe2O3), hydrated goethite (α-FeOOH) and Prussian blue.
5. The cementitious cooling paint according to claim 1 or 4, wherein the structural filler comprises nanoparticles having an average particle size ranging from 0.3 μm to 2 μm.
6. The cementitious cooling paint according to claim 1, wherein the water-absorbing polymer is at least one polymer selected from the group consisting of sodium polyacrylate, sodium carboxymethyl cellulose and sodium alginate, sodium alginate, polyvinyl alcohol, hydroxypropyl methyl cellulose and carboxymethyl cellulose.
7. The cementitious cooling paint according to claim 1, wherein the water collecting material is at least one material selected from the group consisting of deliquescent salts such as lithium chloride (LiCl) and calcium chloride (CaCl2) and hygroscopic polymer materials.
8. The cementitious cooling paint according to claim 2, wherein the dispersant is at least one material selected from the group consisting of sodium polyacrylate and superplasticizers such as sulfonated naphthalene formaldehyde condensates, sulfonated melamine formaldehyde condensates, acetone formaldehyde condensates, and polycarboxylate ethers.
9. A cementitious cooling building material, comprising: Composite cement; Structural packing; Water-absorbing polymers; water collection materials; dispersants; and water; The mass ratio of the water to the composite cement is 0.5 to 1.
5. The mass ratio of the composite cement to the structural filler is 0.4 to 0.7; The mass ratio of the composite cement to the water-absorbing polymer is 0.01 to 0.03; The mass ratio of the composite cement to the water collecting material is 0.05 to 0.3; and The mass ratio of the composite cement to the dispersant is 8 to 15.
10. The cementitious cooling building material according to claim 9, further comprising alkaline water for hydrating the cementitious cooling building material and preventing the cementitious cooling building material from cracking.
11. The cementitious cooling building material according to claim 9, wherein the composite cement is at least one cement selected from the group consisting of different types and grades of Portland cement and geopolymer cement.
12. The cementitious cooling building material according to claim 9, wherein the structural filler is at least one material selected from the group consisting of silicon dioxide (SiO2), barium sulfate (BaSO4), calcium carbonate (CaCO3), zinc oxide (ZnO), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), iron (III) oxide (Fe2O3), hydrated goethite (α-FeOOH) and Prussian blue.
13. The cementitious cooling building material according to claim 9 or 12, wherein the structural filler comprises nanoparticles having an average particle size ranging from 0.3 μm to 2 μm.
14. The cementitious cooling building material according to claim 9, wherein the water-absorbing polymer is at least one polymer selected from the group consisting of sodium polyacrylate, sodium carboxymethyl cellulose and sodium alginate, sodium alginate, polyvinyl alcohol, hydroxypropyl methyl cellulose and carboxymethyl cellulose.
15. The cementitious cooling building material according to claim 9, wherein the water collecting material is at least one material selected from the group consisting of deliquescent salts such as lithium chloride (LiCl) and calcium chloride (CaCl2) and hygroscopic polymer materials.
16. The cementitious cooling building material according to claim 9, wherein the dispersant is at least one material selected from the group consisting of sodium polyacrylate and superplasticizers such as sulfonated naphthalene formaldehyde condensates, sulfonated melamine formaldehyde condensates, acetone formaldehyde condensates, and polycarboxylate ethers.
17. The cementitious cooling building material according to any one of claims 9 to 16, wherein the cementitious cooling building material has a viscosity suitable for manufacturing a cement-based building product selected from cooling tiles, cooling bricks, cooling concrete, cooling concrete blocks, cooling concrete slabs and cooling cement walls.
18. A cement-based building product comprising the cementitious cooling building material according to claim 9, wherein the cement-based building product is one selected from cooling tiles, cooling bricks, cooling concrete, cooling concrete blocks, cooling concrete panels and cooling cement walls.
19. A set of components containing the cementitious cooling paint as defined in claim 1, comprising: a first part, the first part comprising a solid mixture consisting of a composite cement and a structural filler; as well as The second part comprises a liquid mixture consisting of a water-absorbing polymer, a water-collecting material, a dispersant and water; wherein The mass ratio of the water to the composite cement is 0.4 to 1.2; The mass ratio of the composite cement to the structural filler is 0.4 to 0.7; The mass ratio of the composite cement to the water-absorbing polymer is 0.01 to 0.03; The mass ratio of the composite cement to the water collecting material is 0.05 to 0.3; and The mass ratio of the composite cement to the dispersant is 20 to 50.
20. A method for manufacturing a cement-based building product comprising the cementitious cooling building material according to claim 9, the method comprising: A solid mixture is prepared by mixing composite cement with structural filler; A liquid mixture is prepared by mixing a water-absorbing polymer with a water-collecting material, a dispersant and water; uniformly mixing the solid mixture with the liquid mixture to prepare a cementitious cooling building material precursor; Hydrate the cementitious cooling building material precursor using alkaline water to prevent cracks from being generated in the cementitious cooling building material precursor; as well as The hydrated cementitious cooling building material precursor is molded into a desired cement-based building product.
21. The method according to claim 20, wherein The mass ratio of the water to the composite cement is 0.5 to 1.5; The mass ratio of the composite cement to the structural filler is 0.4 to 0.7; The mass ratio of the composite cement to the water-absorbing polymer is 0.01 to 0.03; The mass ratio of the composite cement to the water collecting material is 0.05 to 0.3; and The mass ratio of the composite cement to the dispersant is 8 to 15.
22. The method according to claim 20 or 21, wherein the composite cement is at least one cement selected from the group consisting of different types and grades of Portland cement and geopolymeric cement.
23. The method according to claim 20 or 21, wherein the structural filler is at least one material selected from the group consisting of silicon dioxide (SiO2), barium sulfate (BaSO4), calcium carbonate (CaCO3), zinc oxide (ZnO), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), iron (III) oxide (Fe2O3), hydrated goethite (α-FeOOH) and Prussian blue.
24. The method of claim 20 or 23, wherein the structural filler comprises nanoparticles having an average particle size in the range of 0.3 μm to 2 μm.
25. The method according to claim 20 or 21, wherein the water-absorbing polymer is at least one material selected from the group consisting of sodium polyacrylate, sodium carboxymethylcellulose and sodium alginate, sodium alginate, polyvinyl alcohol, hydroxypropyl methylcellulose and carboxymethylcellulose.
26. The method according to claim 20 or 21, wherein the water collecting material is at least one material selected from the group consisting of deliquescent salts such as lithium chloride (LiCl) and calcium chloride (CaCl2) and hygroscopic polymer materials.
27. The method according to claim 20 or 21, wherein the dispersant is at least one material selected from the group consisting of sodium polyacrylate and superplasticizers such as sulfonated naphthalene formaldehyde condensates, sulfonated melamine formaldehyde condensates, acetone formaldehyde condensates, and polycarboxylate ethers.
28. The method according to any one of claims 20 to 27, wherein the cement-based building product is one selected from cooling tiles, cooling bricks, cooling concrete, cooling concrete blocks, cooling concrete panels and cooling cement walls.
Citation Information
Cited By
Preparation method of magnesium-based gel material with good radiation cooling performance
CN121044881A
Building external facade cooling material based on lithium chloride and preparation method thereof
CN122168068A